2020
DOI: 10.21203/rs.3.rs-29275/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficiency in Aim2 affects viability and calcification of vascular smooth muscle cells from murine aortas and Angiotensin-II induced aortic aneurysms

Abstract: Background: Phenotypic transformation of vascular smooth muscle cells is a key element in vascular remodeling and aortic aneurysm growth. Previously, deletion of several inflammasome components decreased formation of aortic aneurysm (AA) in the Angiotensin II (AngII) -induced mouse model. We hypothesized that the inflammasome sensor Absent in melanoma 2 (Aim2) might affect the phenotype of vascular smooth muscle cells (VSMC), thereby reducing AA formation. Methods : Aim2-/- mice and wild-type (WT) C57Bl/6J mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It was reported that AIM2 could inhibit the viability and increase the apoptosis rate of colorectal cancer (CRC) cells through suppressing the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway [33] . It was also reported that the de ciency of AIM2 could decrease the viability and calci cation of vascular smooth muscle cells from murine aortas [34] . The knockdown of AIM2 could result in reduction of viability in cutaneous cell carcinoma (cSCC) cells and onset of apoptosis [35] .…”
Section: Discussionmentioning
confidence: 94%
“…It was reported that AIM2 could inhibit the viability and increase the apoptosis rate of colorectal cancer (CRC) cells through suppressing the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway [33] . It was also reported that the de ciency of AIM2 could decrease the viability and calci cation of vascular smooth muscle cells from murine aortas [34] . The knockdown of AIM2 could result in reduction of viability in cutaneous cell carcinoma (cSCC) cells and onset of apoptosis [35] .…”
Section: Discussionmentioning
confidence: 94%
“…As the final common pathway of VC, cell phenotype transformation is the ultimate cause of VC 30 . The overexpression of bone‐associated factors and decreased expression of contractile markers are associated with the phenotype transition of VSMCs from smooth muscle cell‐like phenotype to osteoblast‐like phenotype 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As the final common pathway of VC, cell phenotype transformation is the ultimate cause of VC. 30 The overexpression of boneassociated factors and decreased expression of contractile markers are associated with the phenotype transition of VSMCs from smooth muscle cell-like phenotype to osteoblast-like phenotype. 31 Furthermore, because ATF4 is the bridge between ERS and VSMCs 32 In our research, for osteoblastic phenotype, ALP, a pro-biomarker of osteoblast-like differentiation, is activated before and persisting in VC.…”
Section: Discussionmentioning
confidence: 99%